Selective far-field addressing of coupled quantum dots in a plasmonic nanocavity - Jianwei Tang (Nature Portfolio, 2018)
Plasmonic nanostructures can tailor excitation and emission for quantum emitters, but generally only for a single emitter. In this work, the authors selectively excite and detect one out of two quantum dots coupled to a deep-subwavelength cavity composed of three gold nanorods assembled into a U-shape.